Counter-Terrorism: Push and Pull Factors Impacting Male Youth Involved in Violent Extremism in Punjab, Pakistan - Tehmina Aslam (IDEA PUBLISHERS, 2020)
The study examines contribution of societal dogmas and extremist religious ideologies pushing the youth to religious extremism. It asses contribution of people’s persuasion and the state’s coercive measures ranging from law enforcement to physical actions to pull the youth return to peace. The study is qualitative for which interviews are conducted with former militants, their relatives, and friends in Sargodha and Jhang, Pakistan. Four main findings are: First, societal dogmas to devote one’s life for a religious cause motivated the youth to resort to extremism. Second, extremist religious ideologies centred upon jihadism to sacrifice one’s life for a religious cause pushed the youth to terrorism. Third, people’s persuasion especially persuasion by families acted as a major pull factor to bringing the youth back to normal life. Fourth, the state’s coercive hand in enforcement of law and order, security operations, jails and other police actions dissuaded the youth to tread further the path of terrorism. Nonetheless, the pull factors such as societal dogmas and religious ideologies played their role in motivating the youth to terrorism. The pull factors such as people’s persuasion and the state’s coercion outclassed them to assert peace thus preventing them from falling into the abyss of terrorism.